1993
DOI: 10.1111/j.1365-2249.1993.tb03350.x
|View full text |Cite
|
Sign up to set email alerts
|

Raised levels of tumour necrosis factor-alpha and neopterin, but not interferon-alpha, in serum of HIV-1-infected patients from Ethiopia

Abstract: SUMMARY Serum levels of tumour necrosis factor‐alpha (TNF‐α). neopterin and interferon‐alpha (IFN‐α) were determined by immunoradiometric assays in 60 HIV‐1+and 20 HIV‐1− subjects from Ethiopia. Swedish samples were used as reference material. The Ethiopian HIV‐1‘ subjects were found to have significantly increased TNF‐α and neopterin, but not IFN‐α levels. Increased levels of TNF‐α and neopterin were frequently found in Ethiopian asymptomatic subjects (37% and 41%). and the concentration increased in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Mild but persistent elevations of neopterin are common in HIV-positive persons not receiving ART [ 17 , 25 ]. Ayehunie et al compared neopterin levels in HIV-positive subjects from Ethiopia and Sweden, and found significantly higher levels in Ethiopians for unknown reasons [ 26 ]. Since TB is a common OI in Ethiopia, which may be missed in routine clinical investigations [ 27 ], it is possible that unrecognized TB could explain the elevated neopterin levels among some participants in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Mild but persistent elevations of neopterin are common in HIV-positive persons not receiving ART [ 17 , 25 ]. Ayehunie et al compared neopterin levels in HIV-positive subjects from Ethiopia and Sweden, and found significantly higher levels in Ethiopians for unknown reasons [ 26 ]. Since TB is a common OI in Ethiopia, which may be missed in routine clinical investigations [ 27 ], it is possible that unrecognized TB could explain the elevated neopterin levels among some participants in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Neopterin is a pteridine produced almost exclusively by monocytes/macrophages in response to stimulation by IFN-g (Fuchs et al, 1991;Henderson et al, 1991;Landmann et al, 1992). Determination of neopterin levels has been used as a marker of active cell-mediated immunity (CMI) in several diseases (Brown et al, 1990;Magalini et al, 1991;Tilz et al, 1992;Ayehunie et al, 1993;Zerlotti et al, 1994). Despite this indication, patients treated with IFN-g did not sustain a CMI response against M. leprae.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological studies in India revealed the presence of HIV-1-infected macrophages in post mortem brains, but an absence of multinucleated giant cells (MNGC) and multifocal microglial nodules, both of which are frequently found in clade B-infected patients (Mahadevan et al 2007). Pro-inflammatory molecules and markers known to be increased among clade B-infected individuals, such as interleukin (IL)-1 α , IL-6, tumor necrosis factor- α (TNF- α ), β 2 -microglobulin, and neopterin have been identified in the serum and plasma of clade C-infected individuals from India and Ethiopia (Ayehunie et al 1993; Kamat et al 2009). Additionally, clade C viral proteins, such as Tat, exhibit distinct clade-specific modulation of neuropathogenic molecules from their clade B counterparts (Campbell et al 2007; Li et al 2008; Mishra et al 2008).…”
Section: Introductionmentioning
confidence: 99%